A Semiotic Analysis of Poem “Perfect” by Samantha King - Pasaribu, Bertha; Maisarah, Ira (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study used to analyze semiotics based on Roland Barthes' theory in Samantha King's poem titled